Implementasi Penyajian Laporan Keuangan Berbasis SAK ETAP Pada Koperasi di Palembang - Efva Gozali; Nilam Kesuma (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2017)
Tujuan penelitian – This study has two main objectives; first, to investigate the implementation of SAK-ETAP based financial statements on cooperatives, second, to observe the constraints faced by cooperatives in implementing SAK-ETAP in the preparation of financial statements.Desain/Metodologi/Pendekatan – The analytical technique used in this research is qualitative which is descriptive comparative, means comparing the accounting treatment applied by the cooperatives with SAK-ETAP.Temuan – The results of this study indicate that SAK-ETAP has not been fully implemented in the preparation of the financial statements, from the 33 cooperatives as objects of this research, only 3 cooperatives have prepared the comprehensive financial statements.Keterbatasan penelitian – Tuliskan secara singkat apa yang menjadi keterbatasan pada penelitian ini, ini yang dapat menjadi pintu masuk penelitian berikutnya.Originality/value – The constraints faced by cooperatives are caused by limited human resources and lack understanding of the implementation of SAK-ETAP